Independent Recognition of Staphylococcus aureus by Two Receptors for Phagocytosis in Drosophila. - Shiratsuchi, A.; Mori, T.; Sakurai, K.; Nagaosa, K.; Sekimizu, K.; Lee, B.L.; Nakanishi, Y. (Journal of Biological Chemistry, 2012)
Integrin ??, one of two ? subunits of Drosophila integrin, acts as a receptor in the phagocytosis of apoptotic cells. We here examined the involvement of this receptor in defense against infection by Staphylococcus aureus. Flies lacking integrin ?? died earlier than control flies upon a septic but not oral infection with this bacterium. A loss of integrin ?? reduced the phagocytosis of S. aureus and increased bacterial growth in flies. In contrast, the level of mRNA of an antimicrobial peptide produced upon infection was unchanged in integrin ??-lacking flies. The simultaneous loss of integrin ?? and Draper, another receptor involved in the phagocytosis of S. aureus, brought about a further decrease in the level of phagocytosis and accelerated death of flies compared with the loss of either receptor alone. A strain of S. aureus lacking lipoteichoic acid, a cell wall component serving as a ligand for Draper, was susceptible to integrin ??-mediated phagocytosis. In contrast, a S. aureus mutant strain that produces small amounts of peptidoglycan was less efficiently phagocytosed by larval hemocytes, and a loss of integrin ?? in hemocytes reduced a difference in the susceptibility to phagocytosis between parental and mutant strains. Furthermore, a series of experiments revealed the binding of integrin ?? to peptidoglycan of S. aureus. Taken together, these results suggested that Draper and integrin ?? cooperate in the phagocytic elimination of S. aureus by recognizing distinct cell wall components, and that this dual recognition system is necessary for the host organism to survive infection.